Physical impairments and activity limitations in people with femoroacetabular impingement: a systematic review. Issue 4 (22nd September 2014) - Diamond, Laura E; Dobson, Fiona L; Bennell, Kim L; Wrigley, Tim V; Hodges, Paul W; Hinman, Rana S
Abstract : Background: Femoroacetabular impingement (FAI) is a morphological hip condition that can cause hip and/or groin pain in younger active adults. Understanding the nature of physical impairments and activity limitations associated with symptomatic FAI is important to evaluate outcomes and guide development of rehabilitation strategies. The purpose of this systematic review was to establish: (1) whether people with symptomatic FAI demonstrate physical impairments and/or activity limitations compared with people without FAI; and (2) whether treatment affects these parameters. Methods: Four databases (Pubmed, CINAHL, SportDISCUS and Cochrane Library) were searched until the 21 June 2013. Studies evaluated measures of physical impairment and/or activity limitations in people with symptomatic FAI and included either: (1) a comparison control group; or (2) a pretreatment and post-treatment comparison. Methodological quality was assessed using the Newcastle-Ottawa Scale. Results: 16 studies were included. The most commonly reported physical impairment was decreased range of motion (ROM) into directions of hip joint impingement. Other impairments included altered sagittal and frontal plane hip ROM during gait, altered sagittal plane hip ROM during stair climbing, and decreased hip adductor and flexor muscle strength. Effects of surgery on physical impairments are inconsistent but suggest improved hip ROM during gait, but not during stair climbing. Squatting depth improves following surgical intervention for symptomatic FAI. Conclusions: People with symptomatic FAI demonstrate physical impairments and activity limitations. Surgical intervention may restore some deficiencies, but not all. Further studies of physical impairment and activity limitation are needed to evaluate outcomes from surgical and conservative interventions and to inform rehabilitation programmes.